The Influence of Service Quality on Guest Satisfaction at the Restaurant of Oakwood Premier Cozmo Jakarta - Anik Yuniati; Yulianti; Alex Setiawan; Marcella Zailanty Destria (The Postgraduate School of Tourism Sahid Polytechnic, 2026)
Purpose: This study was conducted to analyse the effect of service quality on customer satisfaction at Oakroom Restaurant, Oakwood Premier Cozmo Hotel Jakarta. The study aims to examine five dimensions of service quality (SERVQUAL), namely reliability, responsiveness, assurance, empathy, and tangibles in the context of the hospitality industry. Research methods: This study uses an associative quantitative approach. Data were collected through questionnaires distributed to 50 respondents who had visited the restaurant at least twice. Data analysis was conducted using validity, reliability, normality, simple linear regression tests, and t-tests using SPSS version 29 software. Result and discussion: The analysis results indicate that service quality has a positive and significant influence on customer satisfaction. This is evidenced by a regression coefficient of 0.353 and a significance value (p) < 0.001. In other words, every increase in service quality will be followed by an increase in guest satisfaction. Among the five dimensions, the responsiveness dimension has been proven to be the most dominant predictor influencing satisfaction. Implication: The practical implication of this research is that the management of Oakroom Restaurant is advised to prioritise improving efficiency and service responsiveness in order to enhance overall customer experience and satisfaction. Academically, these findings can serve as a basis or reference for further research exploring the relationship between service quality and satisfaction in the hospitality industry.